Effect of biologic treatments on growth in children with juvenile idiopathic arthritis: A systematic review - Yasmine Makhlouf; Hiba Ben Ayed; Saoussen Miladi; Hiba Boussaa; Kawther Ben Abdelghani; Alia Fazaa; Ahmed Laatar (PLoS ONE, 2025)
Children with Juvenile idiopathic arthritis (JIA) often experience growth retardation due to various factors. The advent of biologic therapies has revolutionized the management of aggressive forms of JIA. This systematic review aims to provide updated insights into the impact of biologic treatments on growth retardation in pediatric JIA patients. Following PRISMA guidelines, we systematically searched Medline, Embase, and the Cochrane Library for eligible articles. Included were cohort studies, trials, and retrospective studies that evaluated growth outcomes in children with JIA receiving biologic therapy. Twelve studies published between 2003 and 2018 were analyzed, encompassing 1513 patients with a mean age of 11.4 years. Tumor necrosis factor alpha inhibitors were the predominant biologic agents used (75.8%), with a mean follow-up duration of 2 years post-biologic therapy initiation. Growth assessment criteria included Height Standard-deviation-score (HSDS), growth velocity, and height velocity (cm/year). Before biologic treatment, 15% of patients exhibited growth delay, while 75.4% had impaired growth. Following biologic therapy, growth delay decreased to 8% and impaired growth to 36.8%. Patients with systemic JIA showed lower changes in growth parameters compared to others, and no significant differences were observed between different biologic drugs. However, lower growth velocity changes were noted in patients treated with multiple biologic agents. Two studies suggested that growth catch-up was most pronounced during the first year of treatment. This systematic review highlights the potential of biologic therapies in mitigating growth impairment associated with JIA. Despite observed positive effects, further research is warranted to elucidate underlying mechanisms and optimize treatment strategies.